Increasing the meat productivity of young sheep based on the use of the gene pool of the Dorper and Hissar breeds - A. Ombayev; Zh. Parzhanov; N. Azhimetov; A. Zhylkibayev; M. Abishov; A. Issabayeva (Brazilian Journal of Biology, 2024)
Abstract In the pursuit of enhanced mutton production, improving the genetic reservoir of sheep with early maturation and high meat productivity is imperative. This study aims to assess the efficacy of integrating Dorper and Hissar rams into the breeding program of Kazakh fat-tailed coarse-haired ewes for generating young mutton. The research involved forming three groups, each comprising 40 ewes of the Kazakh fat-tailed coarse-haired breed, based on analog pairs. Ewes in Group I were inseminated with Dorper ram semen, those in Group II were inseminated with Hissar ram semen, and Group III served as a control with purebred Kazakh fat-tailed coarse-haired sheep breeding. Results revealed that crossbred rams in Group II achieved a significantly higher live weight of 45.2 kg at 120 days of age, surpassing the other groups by 9.7 kg and 10.6 kg. Crossbred gimmers in Group II reached a live weight of 42.0 kg by 4 months, outpacing the other groups by 12.2 kg. The crossbred lambs exhibited an expansive, deep, and sturdy physique, indicative of elevated meat productivity. Physique index analysis displayed that crossbred rams exhibited elongated limbs, bulkiness, and massiveness compared to purebred Kazakh fat-tailed coarse-haired lambs. In the 4.0-4.5-month age range, crossbred rams demonstrated a higher carcass muscle yield than their purebred counterparts, albeit the latter exhibited a 0.18% greater bone yield. Moreover, the meat of groups I and II sheep contained 19.6% and 20.1% protein content, respectively, surpassing the local Kazakh fat-tailed sheep population by 0.7% and 1.2% in absolute terms.